Marketing de influência e NFT’s: aascensão da coleção Bored Ape Yacht Club impulsionada pelas celebridades - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This research addresses concepts of the creative economy, artificial intelligence and influencer marketing. The Bored Ape Yacht Club collection “the bored monkeys” (non-fungible digital images generated by an algorithm and stored on the ethereum blockchain), created by the company Yuga Labs, gained appreciation from celebrities, among them the singer Justin Bieber. The collection of 10.000 tokens launched in April 2021 sold out in one month its entire stock of Bored Ape images available on the Opensea market, from this event, several factors influenced the popularization of NFT's. The approach to the general objective seeks to understand the first year after the launch of the collection and characterize the categories of influencer marketing in the popularization of NFT's, in order to answer the following problem: what are the characteristics of influencer marketing used by celebrities in the appreciation of the collection BAYC and popularization of non-fungible tokens in the community?. The methodologies used were bibliographic review and documentary research, bringing authors such as Kotler (2017), Chohan (2021), Cozman (2021), Howkins (2013), Recuero (2014) and Taulli (2020). The main results obtained by the analysis contemplate the initial question with the support of the influencer marketing categories by scoring which were the actions on Justin Bieber's social networks that impacted on the popularization of the collection. The research is concluded from the perspective of the influence generated by Justin and the actions taken by the company Yuga Labs during the sales activity of the collection, before the community of investors of digital assets.
Keywords: Influência social; Inteligência artificial; Marketing; Bored Ape Yacht Club; Social influence; Artificial intelligence; CNPQ::CIENCIAS SOCIAIS APLICADAS